Exploring engagement and value creation in health social marketing : a service perspective - Luca, Nadina Raluca (2015)
Complex social problems (the continued rise in chronic disease; resource depletion, inequality etc.) call for new social marketing frameworks to accommodate midstream and upstream action which requires collaborations with multiple actors (government, public and private sector). Service-dominant logic (SDL) (Vargo and Lusch, 2004) theoretical developments (systems thinking, value creation, networks etc.) suggest a good compatibility with the collaborative approaches required by midstream and upstream social change (Russell-Bennett, Wood and Previte, 2013). This thesis interrogates the applicability of SDL concepts (value creation and actor engagement) to social marketing. This study focuses on examining the factors influencing engagement, actor motivation and perceived value in a health social marketing context. The study adopts a case study approach and draws upon interviews, observation and document analysis to examine a Smokefree homes and cars programme (‘Smokefree’) in a city in England.